Enhancing Local Economies through Community-Based Tourism: Preserving Cultural Distinctions - Hastiani, Rr. Kamila; Karamina, Batrisyia; Andriyani , Andriyani; Wati, Intan Ratna (Research Horizon, 2024)
Community-Based Tourism (CBT) is one of the sustainable strategies that can strengthen local economies through the promotion of localities' distinctive cultural assets. However, a lack of resources and awareness causes many communities to struggle with effectively using their cultural riches. This study explores how CBT can utilize cultural distinctiveness to improve the local economy. Data were gathered through a literature review on community-based tourism, which includes various types of literature on the topic. This study examines how collaboration between government, cultural preservation, and local involvement might help establish sustainable tourism practices. The findings indicate that localities that incorporate their own distinctive cultural legacy into tourist attractions not only attract a greater number of tourists but also offer up additional sources of revenue, particularly for small businesses and craftsmen. Sustainability also depends on collaboration with other parties and proactive engagement in the community. By providing helpful insights into how cultural distinctiveness might promote economic growth through tourism while maintaining cultural preservation, this study offers suggestions for policy to improve the implementation of CBT.